Adjugate pairs of sparse arrays for sampling two dimensional signals - Vaidyanathan, P. P.; Pal, Piya (2011 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP), 2011)
Sparse sampling with coprime lattice arrays was introduced recently in the literature. It has been shown that a dense coarray can be constructed from such a pair of arrays, and is useful in array processing and image processing applications. For example, the coarray allows one to identify many more sources than sensors. After a brief review of these fundamentals, this paper examines the case where the two arrays are generated by matrices that are adjugates of each other. In this case it is possible to obtain a dense rectangular tiling of the 2D frequency plane from a pair of coarse 2D DFT filter banks. The special case where the adjugate pairs are generated by skew circulant matrices has some advantages, which are examined in detail.